TAHAP KEFAHAMAN PENGGUNA TERHADAP PENSIJILAN HALAL PRODUK MAKANAN RINGAN DI KEDAI SERBANEKA ECO: The User's Understanding Level of Halal Certification for Snack Foods at Eco Convenience Stores - Mohammad Rosli, Alfi Najmi; Nabil, Nurutthoilah Mohd; Mohd Zulkifli, Hidayatul Sakinah; Roslan, Nurul Husna (Selangor Humaniora Review, 2024)
The halal logo is a symbol indicating that a product or service complies with halal standards according to Islamic principles. One of the challenges faced by the Malaysian halal industry is the misuse of the halal logo by traders and the high reliance of the community on the halal logo, which affects the sensitivity and understanding of halal logo issues. The assurance of Muslim consumers regarding the halal status of products is still unsatisfactory due to fake logos items are still widely distributed in the market. Therefore, the objective of this study is to analyse the type of halal certification used, examine the importance of halal certification, and identify the level of understanding of users regarding halal certification of snack foods at Eco Shop. This study uses a mixed-method approach, both qualitative and quantitative for qualitative methods, the researcher utilized document analysis of halal certification for snacks at Eco Convenience Store, while for quantitative methods, the researcher employed descriptive analysis by distributing a questionnaire through Google Forms to gather research data from 346 respondents. The data was then collected using IBM Statistical Package for Social Science (SPSS) version 29.0 in a descriptive format. The importance of this study's findings lies in serving as a guide for stakeholders in efforts to educate users on the significance of halal certification for snack foods.